PREDICTIVE VALUE OF DIGITAL RECTAL EXAMINATION FOR PROSTATE CANCER DETECTION IS MODIFIED BY OBESITY - Chu, David I. (Prostate Cancer Prostatic Dis, 2011)
The American Cancer Society’s updated screening guidelines for prostate cancer (CaP) render digital rectal examination (DRE) optional. We investigated the impact of DRE on CaP detection among obese men. Data from 2794 men undergoing initial prostate biopsy at three centers were analyzed to assess CaP risk attributed to abnormal DRE across body-mass index (BMI) categories. Predictive accuracies of a combination of PSA, age, race, center, and biopsy year including or excluding DRE findings were compared by areas under the receiver-operating characteristics curves (AUC). In all cohorts, obese men were less likely to have abnormal DREs diagnosed than non-obese men. As BMI category increased, abnormal DREs became stronger predictors for overall CaP in individual (p-trends≤0.05) and combined (p-trend<0.001) cohorts, and for high-grade CaP in the Italian (p-trend=0.03) and combined (p-trend=0.03) cohorts. DRE inclusion improved the predictive accuracy for overall and high-grade CaP detection among all obese men (p≤0.032) but not normal-weight men (p≥0.198). DRE inclusion also near-significantly improved overall CaP detection in obese men with PSA<4ng/mL (p=0.081). In conclusion, the predictive value of DRE is dependent on obesity and is significantly higher among obese men than normal-weight men.